THE USING THIEVES STRATEGY TO TEACH READING COMPREHENSION TO EIGHTH GRADE STUDENTS OF SMPN 9 KENDAR - Injar Lasitiha, Hasmirawati (EDUTECH CONSULTANT, 2019)
The objective of this research is to investigate is there a significant difference in students’ reading comprehension between those taught using THIEVES strategy and those attending conventional instruction and also to investigate the motivation and students’ perception in reading comprehension. This research applied treatment and control class with mix method design which analyzed using quantitative and qualitative analysis. The hypothesis of the research is there a significant difference in students’ reading comprehension between those taught using THIEVES strategy and those attending conventional instruction. Using independent t-test to evaluate the hypothesis of the research (sig.2-tailed = 0.00<0.05), reveals that there is a significant difference of reading comprehension between those taught using THIEVES strategy and those attending conventional instruction. This research also covers the students’ motivation in reading comprehension between THIEVES strategy and conventional instruction . The result of my research is there is no significant difference between those taught using THIEVES strategy and conventional instruction and motivation in treatment classes that using treatment THIEVES strategy those increased than conventional instruction or control class. In perceived about these strategies the students prefer in treatment class or using THIEVES strategy.